Leadership Role in Project Management When Implementing the 4th Industrial Revolution Requirements - Aljneibi, Noura (2020)
This research discusses the changes that occurred as a result of the 4th industrial revolution and how it is impacting the project management profession, with a highlight on leadership role in implementing the 4th industrial revolution requirements. This research paper provides a framework illustrating the relationship between the 4th industrial revolution and the leadership skills that a project manager needs to take into account. This research is important because it discusses today’s world and the developments we witness, with focus on the project management field. Also, it highlights one of the most important factors that contributes to this evolution which is leadership. This work attempts to provide an integrated framework and recommendations to avoid the 4th industrial revolution’s negative impacts in the project management field that could be in the form of fewer job opportunities or the inability of the staff to keep up with the technological changes. As this research tries to make the best out of these advancements and developments by engaging leadership to better serve the people and the project management field while taking into account the 4th industrial revolution requirements. Furthermore, this research shows the correlation between the project management skills and the 4th industrial revolution, as well as a regression analysis to know the effect of independent variable on the dependent variable. Correlation and regression analysis have been proven using SPSS analysis that depends on the findings of the survey that has been conducted. The results of the correlation analysis show that there is no significant relationship between (communication, critical thinking, decision making, quality management) and the 4th industrial revolution, however, it shows that there is a statistically significant relationship between (leadership) and the 4th industrial revolution. The results explain the importance of leadership in project management when implementing the requirements of the 4th industrial revolution, and how these two factors (leadership and industry 4.0) are connected to contribute to the project management prosperity. Whereas regression analysis proved that one of the independent variables which is (decision making) has a statistically significant effect on leadership. This work aims to develop the project management field by paying attention to leadership while applying the 4th industrial revolution requirements.